Identification of Apis dorsata Bee Nesting Plants in Natural Forest of Lalang Village Sanggau Regency - Kiki Supriyadi; Gusti Hardiansyah; Fathul Yusro; Yeni Mariani (Jurnal Biologi Tropis, 2022)
Apis dorsata is known as a forest bee that is very productive in producing honey. These bees can make nest combs only by relying on tree branches or branches. This study aims to identify the type of plant where Apis dorsata nests in the natural forest of Lalang Village, Meliau District, Sanggau Regency. This research was conducted using a survey method through interviews with respondents and site surveys to identify and measure tree height, tree diameter, and branch-free stems of the plant species where Apis dorsata bees nest. The data obtained is further analyzed and the results are presented in the form of tables and graphs. The results of our study found that there were 16 species of plants belonging to 8 families as Apis dorsata beehives. The family and names of these plants are Dipterocarpaceae (Anisoptera marginata, Shorea laevis, Dryobalanops lavevis, Dryobalanops beccarii, Anisoptera megistocarpa, Shorea parvifolia, Shorea leprosula), Fabaceae (Inga sp, Millettia borneensis, Koompassia sp, Koompassia excelsa), Apocaceae (Alstonia pneumatophora), Datiscaceae (Octomeles sumatrana), Lauraceae (Litsea sp), Malvaceae (Pterocymbium tubulatum), and Moraceae (Artocarpus sp). The dominant family is Dipterocarpaceae. The total height of Apis dorsata honeycomb trees is the most dominant (75%) in Lalang Village ranging from ±65-90 m, 10 species of sympodial branching (62.5%), and 68.75% of the trunk diameter found ranged from 50-159 cm.